Adaptation Atlas Notebook: Identify Vulnerable Regions - Youngberg, Brayden; Vyas, Shalika; Steward, Peter Richard; Rosenstock, Todd Stuart; Muller, Lolita; Lang, Hannah Helene; Mwakazi, Johnson (2025)
This notebook looks at how climate change vulnerability varies across regions and populations by integrating climate hazards with social and economic conditions. It analyzes vulnerability through three dimensions: exposure to climate hazards, population sensitivity, and adaptive capacity. Using interactive maps and demographic breakdowns, the notebook highlights how agricultural livelihoods, poverty, education, and gender intersect with droughts, heatwaves, and floods across Sub-Saharan Africa. The notebook follows a methodology similar to ND-GAIN to develop a final vulnerability index comprised of the three domains and their sub-variables. By identifying regions with high production value at risk, socially vulnerable groups, and gaps in critical services such as electricity and water access, the notebook supports inclusive, evidence-based adaptation planning and helps guide investments toward the people and places that are most vulnerable.